APPLICATION OF POC FORMULATION FROM BANANA PEEL WASTE AND PATIN FISH OFFAL IN Lemna sp AND GOURAMI (Osphronemus goramy) CULTIVATION MEDIA - Ramadhan, Dandi; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The gourami (Osphronemus gouramy) cultivation faces challenges in terms of relatively slow growth. Lemna sp. plants can be a natural food for gourami and improve water quality to support gourami cultivation. However, Lemna sp. plants require NPK elements that can come from POC formulations from banana peel waste and catfish offal. This study aims to determine the effect of POC formulations from banana peel waste and catfish offal on Lemna sp biomass and to determine the best dose of POC formulations from banana peel waste and catfish offal on Lemna sp and goramy cultivation media. The research was conducted from August to November 2024 at the Hatchery and Environmental Quality Laboratory of Aquaculture, Faculty of Fisheries and Marine Sciences, Universitas Riau. The experimental study used a completely randomised design (CRD) with four treatments and three replicates. The treatments used were P0 (as control), P1: 1.625 mL/L, P2: 2.625 mL/L, and P3: 3.625 mL/L. The results showed that POC formulations from banana peel waste and catfish offal affected Lemna sp.'s biomass and goramy's growth. With treatment P1 (1.625 mL/L), the best dose was in Lemna sp. cultivation media and gourami (with treatment P1 (1.625 mL/L). Treatment P1(1,625 mL/L) is the best dose on the biomass of Lemna sp, which amounted to 767.47 g/m2, and the specific growth rate of Lemna sp. plants of 6.17%/day